The Integration of Health and Social Care in the UK : Policy and practice - Birrell, Derek; Heenan, Deirdre Anne (London : Palgrave, 2018)
Closer integration of health and social care with the aim of ending the historic divide between NHS and social services has been the goal of successive governments for decades. The rationale for greater integration has been widely accepted in terms of service improvement, better use of resources and meeting the needs arising from future demographic change. The debate about integration continues to dominate government papers and reports - and in 2010 the coalition government set out its intention to break down the barriers between health and social care funding to encourage preventative action. This text provides a systematic assessment of recent policy developments across the UK and introduces the different models of integration which currently operate - from structural integration in Northern Ireland to health and care partnerships in Scotland.
Includes QR code.
Includes bibliographical references and index.
Keywords: Integrated delivery of health care -- Great Britain; Social service -- Great Britain -- Methodology; Society